A REVIEW ON ETHNOMEDICINAL USES, PHYTOCHEMISTRY AND PHARMACOLOGICAL PROPERTIES OF COCCULUS HIRSUTUS (L.) DIELS AND COCCULUS PENDULUS (FORST) DIELS (International Association of Biologicals and Computational Digest, 2023)
Menispermaceae is an important angiosperm family containing several medicinally important plants including Cocculus. This review presents a comparative report of two species of this genus, namely, Cocculus hirsutus (L.) Diels and Cocculus pendulus(J. R. Forst. & G. Forst.) Diels. While both species are immensely used by the tribal folk in various forms, they are also abundantly utilised in western medicine. Phytochemical analysis of both species report the presence of several important phytochemicals like alkaloids, flavonoids, terpenoids, phenols, sterols, etc. The pharmacological studies of C. hirsutus(L.) and C. pendulus (Forst)report that the plants contain many properties such antibacterial, anticancer, antiviral, wound-healing, diuretic, analgesic, among others that are quite beneficial to human health. Though much analysis and research work has been reported for Cocculus hirsutus(L.), there are yet many studies to be done on the aspects of Cocculus pendulus (Forst).
Keywords: Cocculus hirsutus(L.); Cocculus pendulus(Forst); ethnomedicinal uses; phytochemical analysis; pharmacological activity; patents